(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
Resorting to the notion of ‘perfomativity’, it is possible to question the issue of genre fixity: in the specific case of ancient theatre, we can identify heterogeneous elements – different from pure dramatic form – which we can label as ‘hybrid’. The habit of systematically describing space and time (referred to as ‘verbal scenography’) has to be seen as a heritage of the epic tradition. In Aristophanes’ comedies, in particular, the protagonist evoke the whole performance reality: he is not only considered as pivotal for the plot by the audience, but also as its creator; a similar phenomenon can be observed in in some kinds of narrative theatre or folk tale. The comic genre always plays open-face and the audience is, in some way, involved in the performance and communication is oriented by its presence. Finally, ancient comedy is able to combine the two different kinds of Aristothelic dramata, dramatic and diegematic poetry.